Modulation of inflammatory response by cortisol in the kidney of spotted scat (Scatophagus argus) in vitro under different osmotic stresses. Issue 104 (September 2020) - Su, Maoliang; Zhang, Ran; Liu, Nanxi; Zhang, Junbin
Abstract: Salinity changes on renal osmoregulation have often been investigated while the immune response of the kidney under osmotic stress is poorly understood in teleosts. Acute stress is generally associated with enhancement of circulating cortisol. The effects of osmotic stress on renal immune response and its regulation by cortisol deserve more attention. In the present study, the effects of exogenous cortisol treatment on the lipopolysaccharide (LPS)-induced immune response were analyzed in renal masses of Scatophagus argus under different osmotic stresses in vitro . mRNA expression of pro-inflammatory cytokines (TNF-α, IL1-β and IL-6) and immune-regulatory related genes (GR and SOCS1) was measured over a short course (15 h). Comprehensive analysis reveals that transcript abundances of pro-inflammatory cytokine genes such as TNF-α, IL-1β, and IL-6 induced by LPS, alone or in the combination of cortisol, are tightly associated with osmoregulation under acute osmotic stress. Our results showed that osmotic challenge could significantly enhance mRNA expression levels of pro-inflammatory cytokines in renal masses in vitro . Based on our analysis, it can be inferred that cortisol suppresses the magnitude of renal inflammatory response and attenuates LPS-induced immune response through GR signaling in the face of challenging environmental conditions. Highlights: Cortisol inhibited LPS-induced immune response through GR signaling under acute stress. mRNA abundances of TNF-α, IL-1β, and IL-6 were tightly associated with osmoregulation under osmotic stress. Transcript profiles of pro-inflammatory cytokines were quite different under ostmotic stress.